Development of a fed batch fermentation strategy to produce bioethanol from non-detoxified hardwood spent sulphite liquor - Bezuidenhout, Niel (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.